Identification of Harmonic Musical Intervals: The Effect of Pitch Register and Tone Duration - ROGALA, Tomira; MIŚKIEWICZ, Andrzej; ROGOWSKI, Piotr (Archives of Acoustics, 2017)
An experiment was conducted to explore the effect of the pitch strength of pure tones constituting a dyad on the accuracy of musical interval identification. Pitch strength was controlled by presenting the intervals in different frequency regions and varying their duration. The intervals were organized into 18 blocks made up by a combination of three octaves: the second (65.4–130.8 Hz), the fourth (261.6–523.3 Hz), and the sixth octave (1047–2093 Hz), and six tone durations, ranging 50–2000 ms in the second octave, and 10–500 ms in the two higher ones. The results indicate that interval identification improveswith increasing pitch strength of the interval’s component tones. The identification scores were much lower in the second octave than in the two higher ones and in all octaves identification worsened as the interval’s duration was shortened. The intervals were most often confused with intervals of similar size rather than with their inversions and intervals of similar sonic character. This finding suggests that the main cue for the identification of harmonic intervals is the pitch distance between two tones. However, in the low pitch range, when the tone pitches are less salient, the impression of consonance may becomea helpful, although not very effective cue.